Impact of municipal wastewater reuse through micro-irrigation system on the incidence of coliforms in selected vegetable crops. (1st December 2019) - Tripathi, Vinod Kumar; Rajput, Thakur Bahadur Singh; Patel, Neelam; Nain, Lata
Abstract: The incidence of coliforms in soil and agricultural produce was evaluated in two vegetable crops, namely, cauliflower and eggplant, which were grown using wastewater for irrigation. Field experiment was conducted at Indian Agricultural Research Institute (IARI), New Delhi, India. In the field experiments to irrigate the crop, municipal wastewater was applied through drip system. The filtration of irrigation water was done through sand media, disk media and their combination. The laterals were placed at surface and subsurface of soil. All filtration processes significantly reduced total coliforms (12–20%) and E. coli (15–25%) populations when evaluated against untreated wastewater. The population dynamics of coliforms in soil profiles indicated that the maximum population of E. coli was estimated on the surface of soil profile when using surface drip, which decreased with soil depth under subsurface placement of drip lateral. After crop harvesting, E. coli in the soil reduced until 20 days after the cessation of irrigation and was highly correlated with soil moisture. E. coli and total coliforms availability were noticed on the surface and in the tissues of leaf and fruit, the coliform count is higher on the surface of plants under surface placement of drip lateral. The concentration of coliforms was lower with eggplant in comparison to cauliflower due to the smooth fruit surface of eggplant. Our study reveals the critical role of subsurface drip irrigation in reducing the load of coliform both in the soil and the crop produce ensuring safety of the consumers against health hazards. In another way protect the environment from wastewater disposal and reduce the burden on synthetic fertilizers as well as shrinking freshwater resources. Highlights: Drip system reduced the load of total coliforms (12–20%) and E. coli (15–25%) counts. E. coli was not detected on the soil surface under subsurface placement of drip laterals. Higher coliform amounts were counted in crushed fruits compared with rinsed fruits.